Lexical Orthographic Knowledge Mediates the Relationship Between Character Reading and Reading Comprehension Among Learners With Chinese as a Second Language - Liao, Xian; Loh, Elizabeth Ka Yee; Cai, Mingjia (Frontiers in Psychology, 2022)
Reading in Chinese is complex because readers should not only recognize characters by basic units (i.e., characters) but also integrate characters into words when reading text. While many efforts have been devoted to investigating the effect of sub-lexical orthographic knowledge in Chinese character reading, less is known about the role played by lexical orthographic knowledge at word level. A total of 424 secondary learners with Chinese as a second language (CSL) in Hong Kong were assessed with character reading, reading comprehension, and two lexical orthographic knowledge tasks: lexical orthographic choice (OKC) and lexical orthographic choice in context (OKCC). Path analysis results demonstrated that these lexical orthographic skills significantly mediated the effect of character reading on comprehension, in which OKCC was a more critical mediator as its mediating effect was bigger than that of OKC. Further analyses showed that these mediating effects were significant only among students with richer learning experience (i.e., learning Chinese for 4 years or above). Our results illustrate the possible trajectory of CSL learners’ literacy development from character reading to reading comprehension and provide pedagogical implications for teaching and learning.